Clinical effects of erythritol, glycine and trehalose as subgingival air-polishing powders on non-surgical periodontal treatment:a systematic review with meta-analysis of randomized controlled trials - Zi-le, Yuan; Yan-xi, Tang; Ying, Zhou; Li, Wenjie; Jun, Chen; Zhou, Meilu (Frontiers in Physiology, 2025)
PurposeThis study aimed to systematically compare the efficacy of erythritol, glycine, and trehalose as subgingival subgingival air polishing powders in non-surgical periodontal treatment (NSPT).MethodsRandomized controlled trials (RCTs) that met the inclusion and exclusion criteria were selected from PubMed, Embase, Web of Science, and Cochrane Library databases (up to August 2024). The sample size, treatment time, and outcome indicators including periodontal probing depth (PPD), clinical attachment level (CAL), and bleeding on probing (BOP) were extracted from the articles. Direct meta-analysis and network meta-analysis were performed by using “R”.ResultsNine RCTs met the inclusion and exclusion criteria. A total of 462 patients were included in the study. For PPD, the network meta-analysis showed that there was no statistical significance in the cross-comparison of erythritol, glycine and trehalose. However, erythritol (SUCRA = 84.1) has an advantage over trehalose (SUCRA = 48.0) and glycine (SUCRA = 28.5) in reducing PPD. The results of direct meta-analysis showed that there was no significant statistical difference in the improvement of outcome indicators such as PPD, CAL and BOP by the three subgingival polishing powders.ConclusionThe recommended order of priority for the use of three subgingival subgingival air polishing powders is as follows: erythritol, trehalose, and glycine.Strenaths and limitaions of this studyWe recommend the priority for the use of the three powders was as follows: erythritol, trehalose, and glycine.Limitations:limited number of RCTs made it difficult to draw a test for publication bias.Systematic Review Registrationidentifier CRD42022366792.